(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: The objective of the study was to evaluate the effectiveness of video assisted teaching on knowledge regarding prevention of shaken baby syndrome among antenatal women and also the association between knowledge with their selected socio-demographical variables. MATERIALS AND METHODS: A one group pre-test and post-test design was adopted. Structured knowledge questionnaire was prepared. The data were collected from 60 women who attend the OPD for antenatal regular checkup using non probability purposive sampling techniques. The reliability of tools was established (0.724).Pilot study was conducted. The data was analyzed and interpreted using descriptive and inferential statistics. RESULTS: The findings revealed that the overall mean pre-test Knowledge score was 11.06 and the overall post-test knowledge score was 19.98 respectively. The mean post-test knowledge score of antenatal women who were exposed to video assisted teaching were significantly higher, than the mean pretest knowledge scores. There was suggestive significance between the knowledge scores and demographic variables. The findings suggest that the video assisted teaching program is an effective teaching strategy to enhance the knowledge of antenatal women, regarding prevention of shaken baby syndrome. CONCLUSIONS: The post-test knowledge score was higher than pretest knowledge score regarding prevention of Shaken Baby Syndrome among antenatal women.The study concluded that, the video assisted teaching Program was an effective teaching strategy, to enhance knowledge of antenatal women regarding prevention of shaken baby syndrome.